Predisposed vulnerabilities and survival among the Finnish soldiers of World War II: historical life course approach - Kivimäki, Ville; Liski, Virva; Taskinen, Ilari (Frontiers in Sociology, 2025)
In this methodological paper we propose a historical life course approach to analyze soldiers’ predispositions to experience war-related violence and stress and to respond to it. We argue that a closer quantitative inspection of pre-war and wartime factors will help to understand the various causes leading to different exposures to stress and violence during the war, which have consequently had different outcomes for the war survivors’ later lives. Our methodology is designed for a rich data source, the Finnish Army in World War II Database (FA2W, N = 4,253), but is generally also applicable to other case studies. We will demonstrate in practice how we apply the historical life course approach to the study of soldiers’ pre-war background variables, wartime service paths, and measurable war stress exposures. In the final discussion, as one potential follow-up to our proposal, we will point to an advanced historical analysis of community-building and meaning-making linked to different war experience profiles combining the quantitative social historical methodology with a qualitative cultural history approach.